CrossFit® open performance is affected by the nature of past competition experiences - Gerald T. Mangine; Jacob M. McDougle (BMC, 2022)
Abstract Purpose To examine the relationships between past competition performances and 2020 CrossFit® Open (CFO) performance. Methods A random selection from the top one thousand athletes (n = 220, 28.5 ± 4.4 years, 178 ± 7 cm, 87.5 ± 10.2 kg) were selected for this study. Overall and weekly performances (including ranks and scores) of the 2020 CFO, as well as overall ranks from all previous CFO, regional, and Games™ competitions in which they competed, were recorded from their publicly available online profile. The highest, lowest, average, and standard deviation (SD) of past rankings, as well as participation statistics (i.e., years since first appearance, total and consecutive appearances, and participation rate), were calculated for each competition stage. Relationships were then assessed between 2020 CFO performance and all past competition experience variables by calculating Kendall's tau (τ) correlation coefficients and Bayes factors (BF10). Results Overall and weekly ranking of the 2020 CFO was extremely favored (p < 0.001, BF10 > 100) to be related to the athlete's highest previous CFO rank (τ = 0.26-0.39) and individual regional appearances (τ = − 0.26 to − 0.34), as well as individual Games™ appearances (overall and for weeks 1, 3, and 4; τ = − 0.20 to − 0.22, p < 0.001, BF10 > 100). Evidence for all other significant relationships ranged from moderate to very strong (p < 0.05, BF10 = 3-100) and varied among specific 2020 CFO workouts. Few associations were noted for team competition experience, and these were generally limited to Games™ appearances (τ = − 0.12 to − 0.18, p < 0.05, BF10 = 3.3-100). Conclusions Although specific relationships were found between 2020 CFO performance and individual appearances at regional and Games™ competitions, the most consistent relationships were seen with participation and ranking in past CFO competitions.